2006
DOI: 10.1128/jvi.00939-06
|View full text |Cite
|
Sign up to set email alerts
|

Postentry Events Are Responsible for Restriction of Productive Varicella-Zoster Virus Infection in Chinese Hamster Ovary Cells

Abstract: Varicella-zoster virus (VZV) is a human alphaherpesvirus that causes chicken pox (varicella) upon primary infection and shingles (zoster) upon reactivation of the virus from latently infected sensory neurons. In contrast to the broad host range of most alphaherpesviruses in cultured cells, productive VZV infection in vitro is restricted almost exclusively to cells derived from humans and other primates (64). Reported exceptions are guinea pig embryonic fibroblasts (62, 64), rabbit kidney cells (64,68), and cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…We found that preincubation of target cells with such agents (e.g., bafilomycin A at 10 nM) prior to the introduction of virus completely blocked infectivity. Similar findings have recently been reported by Finnen et al (14). Although this is compatible with a role for endosomal acidification in viral fusion, alternative explanations include a change in the trafficking of viral receptors following endosomal alkalinization.…”
Section: Cholesterol Depletion Does Not Prevent Surface Expression Orsupporting
confidence: 73%
See 1 more Smart Citation
“…We found that preincubation of target cells with such agents (e.g., bafilomycin A at 10 nM) prior to the introduction of virus completely blocked infectivity. Similar findings have recently been reported by Finnen et al (14). Although this is compatible with a role for endosomal acidification in viral fusion, alternative explanations include a change in the trafficking of viral receptors following endosomal alkalinization.…”
Section: Cholesterol Depletion Does Not Prevent Surface Expression Orsupporting
confidence: 73%
“…Some evidence was recently provided that VZ virion entry into a nonpermissive cell type depends on a low-pH compartment, since it was partially inhibited by lysosomotropic agents (14). We sought to clarify whether VZ virions gain entry by fusing directly with the plasma membrane or instead undergo endocytosis prior to fusion with the membrane delimiting an intracellular compartment.…”
mentioning
confidence: 99%
“…An emerging theme in herpesviral entry is that cellular endosomal pH is required, often in a cell-specific manner (23,30,40,41,46,50,63). gB conformation change is central to the molecular understanding of why herpesviruses require low pH to initiate infection.…”
Section: Discussionmentioning
confidence: 99%
“…MCF12A human mammary epithelial cells were cultured, as previously described (26), in either 5% horse serum or 5% fetal bovine serum (FBS). NIH3T3 mouse fibroblasts were cultured as described (27). Stable clones in both of these cells lines were generated by transfection with a Six expression plasmid SIXFL (14) or pcDNA3.1(CAT) (Invitrogen), followed by selection in 400 Ag/mL G418.…”
Section: Methodsmentioning
confidence: 99%